E-learning Adoption and Use Hype Cycle during Covid-19 Outbreak (A Longitudinal Survey) - Nurdin, Nurdin; S. Pettalongi, Sagaf; Askar, Askar; Hamka, Hamka (Universitas Sebelas Maret, 2021)
Both students and lecturers experience e-learning adoption and use hype, and it has replaced the conventional learning method due to the covid-19 outbreak. However, it is limited known how the e-learning adoption rate is changed and improved during the covid-19 outbreak. This study conducted a monthly longitudinal survey from late March to late June 2020 to find out the e-learning adoption and use hype rate. We randomly distributed 130 questionnaires to students and teaching staff within four faculties at State Islamic University (UIN) of Datokarama Palu. Our study found that during the early covid-19 outbreak, e-learning was reluctantly adopted by both students and lecturers due to a lack of familiarity and technological skills. However, after the third round survey, we found that the hype of e-learning use reached its peak for both students and lectures. In the final round survey, the lecturers' hype to adopt and use e-learning was increased to a plateau of productivity where mainstream adoption starts to take off, and e-learning has been used for more teaching productivity purposes. However, the economy's perception was becoming more challenging to students due to the higher cost of Internet connection, while institutions did not fully provide free Internet access. We also found that there is a perception of the students that e-learning is less meaningful compared to face-to-face learning mechanisms. The limitation of this study is that the study was conducted only in one Islamic higher education institution and the covid-19 outbreak is still ongoing. Therefore, further studies might be required to study more samples and more extended periods to produce more valid results.